Pressure-induced phase transformation in zircon-type orthovanadate SmVO4 from experiment and theory. (6th January 2016) - Popescu, C; Garg, Alka B; Errandonea, D; Sans, J A; Rodriguez-Hernández, P; Radescu, S; Muñoz, A; Achary, S N; Tyagi, A K
Abstract: The compression behavior of zircon-type samarium orthovanadate, SmVO4, has been investigated using synchrotron-based powder x-ray diffraction and ab initio calculations of up to 21 GPa. The results indicate the instability of ambient zircon phase at around 6 GPa, which transforms to a high-density scheelite-type phase. The high-pressure phase remains stable up to 21 GPa, the highest pressure reached in the present investigations. On pressure release, the scheelite phase is recovered. The crystal structure of the high-pressure phase and the equations of state for the zircon- and scheelite-type phases have been determined. Various compressibilities, such as the bulk, axial and bond compressibilities, estimated from the experimental data are found to be in good agreement with the results obtained from theoretical calculations. The calculated elastic constants show that the zircon structure becomes mechanically unstable beyond the transition pressure. Overall there is good agreement between the experimental and theoretical findings.